HF-ERW의 용접 입열량 변화에 따른 용접기 발진 주파수 변화와 개재물 생성 거동의 관계 - 하정우; Jung-woo Ha; 김성웅; Sung-woong Kim; 변우진; Woo-jin Byeon; 손호상; Ho-sang Shon (대한금속·재료학회지, 63(9), 2025)
In this study, High-Frequency Electric Resistance Welding (HF-ERW) phenomena were investigated by measuring variations in the oscillation frequency. Changes in welding phenomenon with welding power involve the formation of a narrow gap and the generation and movement of a bridge. These consequently affect the length of the current path. The change in the current path length results in a variation in the resonance oscillation frequency of the high-frequency welding power supply. By analyzing the oscillation frequency variations, three key characteristic parameters were extracted: Peak Prominence, Strength of Heat Input, and the number of Detected Peaks. The combination of these three parameters allows the prevailing welding phenomenon to be identified. A cold weld is indicated when all three parameters exhibit low values. Normal welding is achieved when the Peak Prominence exceeds a certain threshold value. Within the normal welding regime, oxidized welding inclusions such as Mn-Si-Al-Ti-Nb-O are formed. Analyses confirmed that as the heat input increases, the content of Mn and O within these inclusions increases, and trace alloying elements like Ti and Nb are also additionally oxidized. These changes can be detected by variations in the slope of the frequency waveform, which reflects the bridge's migration speed. By interpreting changes in welding phenomena caused by external factors and variations in welding conditions through oscillation frequency waveform analysis, this research can help enhance HF-ERW weld integrity.